An epidemiological study of suspected rabies exposures and adherence to rabies post-exposure prophylaxis in Eastern Thailand, 2015. - Onphirul Yurachai; Soawapak Hinjoy; Ryan M Wallace (Public Library of Science (PLoS), 2020)
BACKGROUND:Human rabies is a notifiable condition in Thailand, and 46 confirmed and probable cases were reported from 2010-2015; eleven were reported from Eastern Thailand. Although rabies is vaccine preventable, more than 90% of persons who died of rabies in Thailand either did not receive or inappropriately discontinued post-exposure prophylaxis (PEP). In 2012 Thailand launched a national animal rabies elimination program with the goal of elimination by 2020. One of the policies of this national program is to improve detection of animal rabies exposures, access to PEP, and adherence to vaccine schedules. To achieve this goal, several hospital-based electronic PEP surveillance systems have been instituted throughout Thailand. METHOD:Data from a voluntary, electronic hospital-based, rabies exposure and PEP surveillance system was analyzed from eight provinces in Eastern Thailand for the time period January 1 -December 31, 2015. The surveillance system collects data from all persons who present to an R36-integrated healthcare facility with a suspected rabies exposure, including characteristics of the biting animals, categorization of the rabies exposure, and adherence to PEP recommendations. The crude rate of healthcare seeking for a suspected rabies exposure was assessed by province, and a multivariable linear regression model was developed to determine the potential extent of undetected rabies exposures due to bite treatment at healthcare facilities that do not utilize the R36 system. Suspected rabies exposures were described by patient demographics, location of wound, and disposition of the offending animal. A comparison of adherence to intramuscular and intradermal vaccination regimens was performed and odds ratios were calculated for factors related to unadvised PEP discontinuation. RESULT:6,204 suspected rabies exposures were reported from eight Eastern Thailand provinces, yielding a crude exposure rate of 106 reported rabies exposures per 100,000 population. When adjusted for under-detection due to non-participating hospitals and province-level demographic differences, the estimated suspected rabies exposure rate was 204/100,000. Dogs were the main source of exposure (77.8%) and children age <15 years and elderly age >60 years had the highest overall reported exposure rate (189.7 and 189.2/100,000). Adherence to either the intramuscular 5-dose or the intradermal 4-dose PEP regimen was low (15.8% and 46.5%, respectively); rabies immunoglobulin was received by only 15% of persons for whom it was indicated. Persons with rabies exposures were more likely to discontinue the vaccination series against medical advice if they were male, aged 16-45, if they received immunoglobulin, or if received the intramuscular regimen. CONCLUSION:When adjusting for number of reporting hospitals, province population density, number of hospitals per population and average family income, the expected report rate increased 1.9-fold, indicating that there is likely a high level of under-detection of persons seeking medical care for suspected rabies exposures. Expanded implementation of electronic surveillance systems will likely improve reporting and the epidemiologic knowledge of rabies exposures. Analysis of data collected from this system revealed very low rates of adherence to rabies vaccination recommendations. PEP adherence was better by the intradermal route, which provides more support for its use in situations where it is economically feasible.